Metode Maisura sebagai Strategi Peningkatan Tahsin Tartil Santri: Studi Kasus di Rumah Tahfidz Ibadurrahman Kota Jambi - Novita, Sukma Ria; Jailani, M Syahran; Idarianty, Idarianty (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The low quality of Qur’anic recitation among students remains a persistent challenge despite increasing memorization achievement. This study addresses the question: to what extent is the Maisura method effective in improving the tahsin tartil skills of students at Rumah Tahfidz Ibadurrahman, Jambi? Employing a descriptive qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation of the tahsin program. The findings reveal a significant improvement across four key indicators: makhraj (52% to 80%), tajwid (48% to 76%), tempo (60% to 82%), and tartil (55% to 78%). The implementation of Maisura through talaqqi musyafahah, repetitive drills, and the use of murottal audio proved effective in producing more accurate and rhythmic recitation. Despite challenges such as a high teacher–student ratio and limited digital facilities, this study highlights Maisura as a strategic method for strengthening Qur’anic recitation quality. Beyond its empirical contribution, the research enriches the academic discourse on Qur’anic pedagogy while offering practical recommendations for the management of modern tahfidz institutions in Indonesia.